Comprehensive Genomic Identification and Expression Analysis of the Phosphate Transporter (PHT) Gene Family in Apple - Sun, Tingting; Li, Mingjun; Shao, Yun; Yu, Lingyan; Ma, Fengwang (Frontiers in Plant Science, 2017)
Abstract Elemental phosphorus (Pi) is essential to plant growth and development. The family of phosphate transporters (PHTs) mediates the uptake and translocation of Pi inside the plants. Members include five sub-cellular phosphate transporters that play different roles in Pi uptake and transport. We searched the Genome Database for Rosaceae and identified five clusters of phosphate transporters in apple (Malus domestica), including 37 putative genes. The MdPHT1 family contains 14 genes while MdPHT2 has two, MdPHT3 has seven, MdPHT4 has 11, and MdPHT5 has three. Our overview of this gene family focused on structure, chromosomal distribution and localization, phylogenies, and motifs. These genes displayed differential expression patterns in various tissues. For example, expression was high for MdPHT1;12, MdPHT3;6, and MdPHT3;7 in the roots, and was also increased in response to low-phosphorus conditions. In contrast, MdPHT4;1, MdPHT4;4, and MdPHT4;10 were expressed only in the leaves while transcript levels of MdPHT1;4, MdPHT1;12, and MdPHT5;3 were highest in flowers. In general, these 37 genes were regulated significantly in either roots or leaves in response to the imposition of phosphorus and/or drought stress. The results suggest that members of the PHT family function in plant adaptations to adverse growing environments. Our study will lay a foundation for better understanding the PHT family evolution and exploring genes of interest for genetic improvement in apple.